The Influence of Physical Environment on Dining Experience among Restaurants - Labrador, Hazel; Tombon, Carla Jean; Dela Cerna, Sweeden; Regidor, Lucela (The Pendulum, 2023)
This study discussed the influence of Physical Environment on Dining Experience among Restaurants in Tagum City. Specifically, this study aimed to determine the significant relationship between the physical environment and the dining experience among restaurants in Tagum City and measure the level of Physical Environment in terms of: Facility Aesthetic, Ambiance, Lighting, Layout, Table Settings, and Service Staff. Along with the level of Dining Experience in terms of: Product, Service, Brand, Consumption, and Emotions. The total number of respondents involved in the online survey were 200 customers of Restaurants in Tagum City. This research uses a quantitative, descriptive research design. Mean, Pearson (r) and Multiple Regression Analysis was used as statistical tools for the data analysis. The result of the Physical Environment and Dining Experience are moderately evident among Restaurant in Tagum City. Moreover, there is a significant relationship between Physical Environments on Dining Experience. Lastly, the domains in Physical Environment which is the Facility Aesthetic, Lighting, Table Settings, and Service Staff, significantly influence the Dining Experience, while the Ambiance and Layout are those that have no significant influence according to the results.